ENVIRONMENTAL AND SOCIAL SUSTAINABILITY IN TEXTILE MANUFACTURING: A REVISED ANALYSIS OF OEKO-TEX 1000 CERTIFICATION IN UZBEKISTAN - Jumayeva Mahliyo Baxtiyor qizi; Mamadaliyeva Dildora Abdumalikovna (Modern American Journals, 2025)
This paper investigates the environmental and social impact of OEKO-TEX 1000 certification in Uzbekistan's textile sector. Through case studies of three certified manufacturers—Bukhara Cotton Textile, Hamzatex, and Monomy—the study evaluates improvements in water and energy efficiency, chemical safety, workplace safety, and export performance. Using a mixed-methods approach, the research combines qualitative interviews, quantitative performance indicators, and document analysis to assess the certification's effectiveness. Results indicate substantial resource savings, enhanced compliance, and increased international competitiveness. Despite initial costs and technological barriers, OEKO-TEX 1000 proves to be a viable model for sustainable industrial development in emerging economies. The study offers policy recommendations to support wider adoption across the sector.
Keywords: OEKO-TEX 1000, sustainability, textile industry, Uzbekistan, certification, resource efficiency, labor standards